Planejamento econômico durante a ditadura militar e seus desdobramentos sobre a economia goiana - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
The economic development plans during the Military Dictatorship period (1964-1985), in Brazil, were fundamental instruments for consolidation of the national industry, for the high rates of economic growth and for the process of productive integration of the states of the federation, including the State of Goiás. Thus, from the analysis of the development programs of the Federal Government and the State Government, it is possible to specify categorically the influences of the first over the second. This way, the objective of this work was to comprehend the unfolding of planning policies during the Military Dictatorship on the economy of Goiás and its influence on state administration programs. For this purpose, we discussed about the process of constituting the Military Dictatorship, the way the links between the economy of Goiás and the national economy during the analyzed period were given and the influence of federal development programs under the state programs of Goiás. The research method used was the historical-dialectic materialism. The methodology adopted was bibliographic and documentary. With that, it was possible to verify that the development programs of the Federal Government had succeed in relation to the established purpose and goals, and, within the national context, the State of Goiás dialogued with the national economic scenario, through the process of agricultural modernization, seeking the increase and diversification of the large-scale production, and the development of other state potentialities, such as ore mining. The cooperation of the Government of the State of Goiás, with the Federal Government, was a determining factor for the consolidation of a subordinate productive integration. The state of Goiás, mainly from the 1970s, onwards, had considerable advances in the productive sector, responsible for a significant part of the national export agenda, fulfilling the role of agricultural and mineral producers.
Economic planning during the military dictatorship and its development on the goiana economy
Keywords: Economia goiana - Planos de desenvolvimento; Economia goiana - Ditadura militar; Economia goiana - Modernização agrícola; Economia - Estado de Goiás; Goiás economy - Development plans; Goiás economy - Military dictatorship; Goiás economy - Agricultural modernization; Economy - State of Goiás; CIENCIAS SOCIAIS APLICADAS::ECONOMIA